The New Arabic Language Book For The Fourth Preparatory (Analytic and Evaluation Studied) - Ahmed Issa Taher ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This research highlights on the linguistic content and its scientific about the new Arabic book for fourth preparatory class. As follows the approach of groups authors, its chapters and its sections with the description and analysis and its evaluation. This research aims to diagnose prose of the book and its advantages to benefit from them in the followed published experiments and stand on placements of bugs, disorder, omissions and forgetting. And alarms on placements of mistakes to statement of the face of right things according to the guidance of the words of Arabs which were come in the inherited of Arabicʼs linguistic and Arabicʼs language and its grammar. At it all that, was an aim of the researcher, his attentions and his intention to help taking out this book in the ideal image. And upgrading with the authoring level in this book